Peyronie's Disease: Evaluation and Review of Nonsurgical Therapy - Michael R. Abern; Laurence A. Levine (The Scientific World Journal)
The purpose of our study was to outline the evaluation of the Peyronie's disease (PD) patient and review the available nonsurgical treatments. A review of the literature on oral, intralesional, external energy, iontophoresis, and mechanical therapies for PD was performed. PubMed was utilized to find all published articles, and several meeting abstracts were reviewed for data ahead of publication. Our medical evaluation of the PD patient is described. The published results of available treatment options are reviewed, with recommendation by the authors for appropriate nonsurgical management of PD. There are no available validated questionnaires for PD, but a thorough history and focused physical examination, including measurement of erect penile deformity, will help the clinician make the diagnosis and guide treatment options. Although there are many published reports that show efficacy of nonsurgical therapies for PD, there is a lack of large-scale, multicenter, controlled clinical trials, which makes treatment recommendations difficult. Careful review of the literature does suggest that there are treatment options that make scientific sense and appear to stabilize the disease process, reduce deformity, and improve function. Offering no treatment at all will encourage our patients to pursue alternative treatments that may do harm, and misses the opportunity to do some good. Clearly, further work is necessary to develop safe and effective nonsurgical treatments for PD.